Hubungan Kadar Hemoglobin dalam Darah Berdasarkan Pola Aktivitas dan Pola Konsumsi Zat Besi Mahasiswi di Politeknik Bina Trada Semarang Tahun 2025 - Gracellda Angelina Pitaloka Wangi; Rina Puspita; Resti Ariani (HB PRESS, 2026)
Anemia remains a common health problem among female students, often associated with low hemoglobin levels due to inadequate iron intake and insufficient physical activity. Female students are a vulnerable group due to menstrual blood loss, irregular dietary patterns, and lifestyle changes. This study aimed to analyze the relationship between physical activity patterns and iron consumption patterns with hemoglobin levels among female students at Politeknik Bina Trada Semarang in 2025. This study used an analytic quantitative design with a cross-sectional approach. The population was all female students at Politeknik Bina Trada Semarang, with a sample of 43 respondents selected using purposive sampling. Inclusion criteria included active female students without diseases affecting hemoglobin levels, while exclusion criteria were those menstruating during data collection. Data were collected using questionnaires for physical activity and iron consumption patterns, and hemoglobin levels were measured using the CuSO? method. Data were analyzed using the Kruskal-Wallis test with a significance level of 0.05. The results showed that 58% of respondents had low hemoglobin levels. Most respondents had light physical activity (53.5%) and rarely consumed iron-rich foods (48.8%). Statistical analysis indicated no significant relationship between physical activity patterns and hemoglobin levels (p = 0.084), as well as between iron consumption patterns and hemoglobin levels (p = 0.373). There is no significant relationship between physical activity patterns and iron consumption patterns with hemoglobin levels among female students. However, both factors remain important in maintaining optimal health and preventing anemia.